Method for judging whether cracks exist in casting blank or not according to end face crack characteristics of casting blank

By conducting acid-immersion and low-power observation on the end surface of the cast blank sample, combined with the microscopic observation of metallographic microscope and scanning electron microscope, we can determine whether the cracks on the end surface of the cast blank extend to the inside, which solves the problem of difficulty in accurately determining whether there are cracks inside the continuous cast large round blank in the prior art, improving detection efficiency and accuracy, and reducing economic losses.

CN119643544APending Publication Date: 2025-03-18SHANXI TAIGANG STAINLESS STEEL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411587648.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to accurately determine whether there are cracks inside the continuous casting large round blank, resulting in low pass rate, high inspection cost, and huge product scrapping and economic losses caused by misjudgment.

Method used

By conducting acid impregnation and low-magnification observation on the end surface of the casting sample, metallographic samples are prepared for microscopic observation, and combined with macroscopic and microscopic observation results, it is determined whether the cracks on the end surface of the casting sample extend to the inside.

Benefits of technology

It improves detection efficiency and accuracy, reduces economic losses, and ensures product safety and quality stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643544A_ABST
    Figure CN119643544A_ABST
Patent Text Reader

Abstract

The invention discloses a method for judging no crack in a casting blank according to casting blank end face crack characteristics. The method comprises the steps that the end face of a casting blank sample is subjected to acid leaching, the acid leaching time is controlled to range from 5 min to 30 min, the temperature of a solution in the acid leaching process is controlled to range from 70 DEG C to 80 DEG C, and the end face of the casting blank obtained after acid leaching serves as a low-magnification observation face to conduct macroscopic observation on the crack; preparing a metallographic specimen for the observed crack on the low-magnification observation surface, carrying out microscopic observation by taking the metallographic specimen as a first section cutting plane, and sectioning the observed crack on the low-magnification observation surface along a preset position in a direction perpendicular to the crack to obtain a second section cutting plane, microscopically observing the trend and shape of the cracks on the first and second section cutting planes, whether metal and nonmetal impurity segregation exists at the cracks, and whether abnormal precipitated phases exist at the crack edge positions of the first and second section cutting planes; whether the cracks exist in the casting blank or not is judged according to the trend and form of the cracks on the low-power observation surface, the first section cutting surface and the second section cutting surface of the casting blank sample, the detection efficiency is high, and economic losses are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel smelting, and in particular to a method for judging whether there are cracks in a billet according to crack characteristics of the billet end surface. Background Art

[0002] The end face cracks of large-sized continuously cast round billets are a key production technology issue studied in the industry. The excessive crack defects found in the low-magnification test specimen of the end face of the billet after sawing, such as the low-magnification cracks of the continuous casting round billet are mainly subcutaneous cracks, middle cracks, center cracks, etc. The existence of the above crack defects will directly lead to the unusability of the billet; for example, YB / T4149-2018 "Continuous Casting Round Billets" stipulates that "the allowable level of low-magnification structural defects such as center cracks, middle cracks, subcutaneous cracks on the low-magnification structural test piece of the cross-section of the billet acid immersion should not be greater than level 2.0, respectively", while the latest enterprise standards of some domestic manufacturers stipulate that the center cracks, middle cracks, and subcutaneous cracks on the low-magnification structural test piece of the cross-section of the continuous casting round billet acid immersion should be level 0, respectively.

[0003] At present, ultrasonic flaw detection is used to detect whether there are cracks inside the continuous casting large round billet. However, due to the coarse as-cast structure of the continuous casting large round billet, it is difficult to accurately and reliably judge the subtle defects inside the continuous casting large round billet by ultrasonic flaw detection. This results in a low qualified rate of the casting billet and a high detection cost. When the internal defects of the continuous casting large round billet are not accurately detected and the next processing step is carried out, the product is often scrapped due to the presence of cracks found during the processing. Or when it is delivered to the order manufacturer, it is impossible to accurately determine whether there are cracks on the end face of the continuous casting large round billet inside it or the crack defect level is judged to be too high, resulting in the cast continuous casting large round billet being directly judged as scrap and returned, which leads to scrapping. This is not only time-consuming and labor-intensive, but also incurs huge manpower costs and causes huge economic losses. Summary of the invention

[0004] In order to solve some or all of the technical problems existing in the above-mentioned prior art, the present invention provides a method for judging whether there are no cracks in the ingot based on the crack characteristics on the end face of the ingot, which solves the problem of judging whether such cracks already exist inside the ingot when it is difficult to determine the presence of low-magnification cracks on the end face of the ingot using ultrasonic flaw detection methods. At the same time, the detection efficiency is high, the detection results are accurate, and the economic losses are reduced.

[0005] The technical solution of the present invention is as follows:

[0006] The present invention provides a method for judging whether there are no cracks in a casting billet according to the crack characteristics of the end surface of the casting billet, comprising:

[0007] The end face of the ingot sample is acid-diluted, the acid-diluted time is controlled to be 5-30min, the temperature of the solution during the acid-diluted process is controlled to be 70-80℃, and the end face of the ingot after acid-diluted is used as a low-magnification observation surface for macroscopic observation of cracks;

[0008] A metallographic specimen is prepared for the observed crack on the low-magnification observation surface and used as a first section surface for microscopic observation, and the observed crack is sectioned along a preset position on the low-magnification observation surface in a direction perpendicular to the crack to obtain a second section surface, and the direction and morphology of the crack on the first section surface and the second section surface are microscopically observed;

[0009] Microscopically observing whether there is segregation of metal and non-metal impurities at the cracks on the first section surface and the second section surface, and whether there is abnormal precipitation phase at the edge of the cracks on the first section surface and the second section surface;

[0010] Whether cracks already exist inside the ingot can be determined based on the direction and shape of cracks on the low-magnification observation surface, the first section surface, and the second section surface of the ingot sample.

[0011] Furthermore, in the above-mentioned method of judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end surface, the cracks include any one or more of the central cracks, middle cracks and subcutaneous cracks on the ingot end surface.

[0012] Furthermore, in the above-mentioned method for judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end surface, acid immersion of the ingot sample end surface includes acid immersion using a corrosive liquid.

[0013] Furthermore, in the above-mentioned method for judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end surface, the corrosive liquid includes a hydrochloric acid aqueous solution with a volume ratio of 1:1.

[0014] Furthermore, in the above-mentioned method for judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end surface, the hydrochloric acid selected in the hydrochloric acid aqueous solution includes a hydrochloric acid solution with a specific gravity of 1.19 g / ml or a concentration of 39%.

[0015] Furthermore, in the above-mentioned method for determining whether there are no cracks in the ingot based on the crack characteristics on the end surface of the ingot, the preset position includes a position at half the length of the crack.

[0016] Furthermore, in the above-mentioned method for judging whether there is no crack in the ingot based on the crack characteristics of the ingot end surface, judging whether the crack already exists inside the ingot based on the direction and morphology of the cracks on the low-magnification observation surface, the first section surface and the second section surface of the ingot sample includes:

[0017] Determine whether the crack morphology on the low-magnification observation surface and the first section surface after acid immersion is a straight line or a linear type;

[0018] Determine whether the crack on the second section surface extends in a zigzag shape along the grain boundary of the as-cast structure, and whether the structures on both sides of the crack on the first section surface and the second section surface can be completely spliced;

[0019] Determine whether there is metal and non-metal impurity segregation at the cracks on the first section surface and the second section surface, and whether there is abnormal precipitation phase at the crack edge position of the first section surface and the second section surface;

[0020] If the morphology of the cracks observed on the low-magnification observation surface and the first section surface after acid leaching is a straight line or a linear shape, the cracks observed on the second section surface crack and expand in a zigzag shape along the grain boundary of the as-cast structure, the structures on both sides of the cracks on the first section surface and the second section surface can be completely spliced ​​together, there is no segregation of metal and non-metallic impurities at the cracks on the first section surface and the second section surface, and there are no abnormal precipitated phases at the crack edge positions of the first section surface and the second section surface, then there are no cracks inside the ingot, otherwise there are cracks inside the ingot.

[0021] Furthermore, in the above-mentioned method of judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end surface, the macroscopic observation includes observation with the naked eye or observation with a magnifying glass of no more than 10 times.

[0022] Furthermore, in the above-mentioned method of judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end surface, the microscopic observation includes observation using a metallographic microscope or a scanning electron microscope.

[0023] The main advantages of the technical solution of the present invention are as follows:

[0024] The method for judging whether there are no cracks in a billet based on crack characteristics on the end face of the billet of the present invention performs transverse low-magnification acid immersion observation and longitudinal section observation on the end face of the large round billet, and the observation angle is more comprehensive. Macroscopic observation and analysis, metallographic microscope and scanning electron microscope microscopic observation and analysis are adopted to gradually analyze the cracks on the end face of the billet from a macroscopic to a microscopic perspective, and the analysis angle is more in-depth, and the result of judging the direction and morphology of the cracks is more accurate. The problem that it is difficult to determine whether such cracks already exist inside the billet when the ultrasonic flaw detection method is used, and at the same time, disposal measures can be proposed according to the cause of the defect to ensure the product safety of the end user. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings described herein are used to provide a further understanding of the embodiments of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0026] Figure 1 It is a schematic flow chart of a method for judging whether there are no cracks in a casting billet according to crack characteristics on the end surface of the casting billet according to an embodiment of the present invention;

[0027] Figure 2A schematic diagram of low-magnification macroscopic observation of the central crack of a wheel steel round billet by acid immersion according to a method for judging that there is no crack in the billet based on the crack characteristics of the billet end surface provided by an embodiment of the present invention;

[0028] Figure 3 for Figure 2 A local enlarged schematic diagram of the crack shown in;

[0029] Figure 4 For along Figure 2 Schematic diagram of the crack on the second section after vertical sectioning at the crack center shown in FIG.

[0030] Figure 5 for Figure 2 Schematic diagram of the metallographic structure of the cross section of the middle crack (second section);

[0031] Figure 6 for Figure 5 The local enlarged schematic diagram of the metallographic structure of the crack cross section shown in;

[0032] Figure 7 To include Figure 5 Schematic diagram of the partially enlarged structure of the end morphology of the middle crack;

[0033] Figure 8 To include Figure 5 Schematic diagram of the local magnified structure of the end of the crack under the scanning electron microscope (SEM);

[0034] Fig. 9 This is a schematic diagram of the continuous casting slab annealing process flow provided in this embodiment. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention and the corresponding drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0036] The technical solution provided by the embodiments of the present invention is described in detail below with reference to the accompanying drawings.

[0037] As attached Figure 1-Figure 9 As shown, an embodiment of the present invention provides a method for judging whether there are no cracks in a billet according to the crack characteristics of the billet end surface, the method comprising:

[0038] The end face of the ingot sample is acid-immersed, the acid immersion time is controlled to be 5-30min, the temperature of the solution during the acid immersion process is controlled to be 70-80°C, and the end face of the ingot after acid immersion is used as a low-power observation surface for macroscopic observation of the crack; a metallographic sample is prepared for the observed crack on the low-power observation surface, and used as a first section surface for microscopic observation, and the observed crack is sectioned along a preset position perpendicular to the crack direction on the low-power observation surface to obtain a second section surface; the direction and morphology of the crack on the first section surface and the second section surface are microscopically observed; whether there is segregation of metal and non-metal impurities at the crack on the first section surface and the second section surface, and whether there is abnormal precipitation phase at the crack edge position of the first section surface and the second section surface; according to the direction and morphology of the crack on the low-power observation surface of the ingot sample, the first section surface and the second section surface, it is judged whether the crack already exists inside the ingot.

[0039] Therefore, the method of judging whether there are no cracks in the ingot based on the crack characteristics of the end face of the ingot of the present invention, through the transverse low-magnification acid immersion observation and longitudinal section observation of the end face of the large round ingot, the observation angle is more comprehensive, and the macroscopic observation and analysis, metallographic microscope and scanning electron microscope microscopic observation and analysis are adopted to gradually analyze the cracks on the end face of the ingot from macroscopic to microscopic perspectives, and the analysis angle is more in-depth, and the results of judging the direction and morphology of the cracks are more accurate, which solves the problem that it is difficult to determine "whether such cracks already exist inside the ingot when low-magnification cracks appear on the end face of the ingot" by using ultrasonic flaw detection method, and at the same time, according to the cause of the defect, disposal measures can be proposed to ensure the product safety of end users.

[0040] In some optional implementations of this embodiment, the above-mentioned metal and non-metal impurity segregation includes but is not limited to elements such as Mn, S and P.

[0041] Specifically, in the method of the present invention for judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end face, the above cracks include but are not limited to any one or more of the central crack, middle crack and subcutaneous crack of the ingot end face.

[0042] Therefore, by observing one or more cracks on the end face of the ingot, it is possible to determine whether the cracks on the end face extend to the interior of the ingot, and thus it is possible to accurately determine whether such cracks already exist inside the ingot, thereby avoiding the problem of scrapping the ingot due to the presence of cracks, causing economic losses.

[0043] Specifically, in the method of the present invention for judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end face, acid immersion of the ingot sample end face includes acid immersion using a corrosive liquid, and preferably the corrosive liquid includes a hydrochloric acid aqueous solution with a volume ratio of 1:1.

[0044] In order to ensure that the hydrochloric acid aqueous solution in the acid leaching process can meet the corrosion requirements for the end face of the continuous casting round billet without damaging the billet, reducing the cost of the corrosive liquid, and reducing the damage to the end face of the billet and surrounding equipment caused by the excessively high concentration of the corrosive liquid, the hydrochloric acid selected in the hydrochloric acid aqueous solution includes a hydrochloric acid solution with a specific gravity of 1.19g / ml or a concentration of 39%.

[0045] Specifically, the preset position includes a position at half the crack length.

[0046] In some optional implementations of the present embodiment, in order to be able to more accurately observe the cracks on the end face of the ingot and determine the direction of the cracks, and determine whether the cracks located on the end face of the continuous casting ingot already exist inside it, the above-mentioned preset position can also be set to one-third, one-quarter or one-fifth of the crack, and one or more cutting surfaces can be set at one-half, one-third, one-quarter or one-fifth of the crack, so as to more accurately judge whether the crack already exists inside the ingot; at the same time, in order to reduce multiple cuttings of the ingot and improve the judgment efficiency, the cutting position and the number of cuttings can be determined according to the length of the crack. For example, when the crack length is relatively short, two cutting surfaces can be set at the equally divided position of the crack. If the crack length is relatively long, at least two or even more cutting surfaces can be set at the equally divided position of the crack. The specific number of section surfaces to be set depends on the length of the crack. For example, if the length of the crack is greater than or equal to the length of Level 1 of "subcutaneous cracks, middle cracks, and center cracks" in YB / T 153-2015 "Rating Chart of Low-magnification Microstructure Defects of High-quality Structural Steel Continuous Casting Billets", it is long, otherwise it is short.

[0047] Specifically, judging whether the cracks already exist inside the ingot based on the direction and morphology of the cracks on the low-magnification observation surface, the first section surface, and the second section surface of the ingot sample includes:

[0048] Determine whether the crack morphology on the low-power observation surface and the first section surface after acid immersion is a straight line or a linear type; determine whether the crack on the second section surface cracks and expands in a zigzag shape along the grain boundary of the as-cast structure, and whether the structures on both sides of the crack on the first section surface and the second section surface can be completely pieced together; determine whether there is segregation of metal and non-metal impurities at the cracks on the first section surface and the second section surface, and whether there are abnormal precipitation phases at the crack edges of the first section surface and the second section surface; if the morphology of the crack observed on the low-power observation surface and the first section surface is a straight line or a linear type, the crack observed on the second section surface cracks and expands in a zigzag shape along the grain boundary of the as-cast structure, the structures on both sides of the crack on the first section surface and the second section surface can be completely pieced together, there is no segregation of metal and non-metal impurities at the cracks on the first section surface and the second section surface, and there are no abnormal precipitation phases at the crack edges of the first section surface and the second section surface, then there is no crack inside the ingot, otherwise there is a crack inside the ingot.

[0049] Therefore, through the above judgment method, when all judgment results meet the judgment conditions, it is determined that there are no cracks inside the ingot. If one or more judgment results do not meet the judgment conditions, there may be cracks inside the ingot, so that the judgment result is inaccurate, and the problem of scrapping due to cracks inside the ingot cannot be solved.

[0050] In some optional implementations of this embodiment, macroscopic observation includes observation with the naked eye or observation with a magnifying glass of no greater than 10 times magnification, and microscopic observation includes observation with a microscope or an electron microscope.

[0051] Exemplarily, the cracks on the above-mentioned low-magnification observation surface can be observed using a magnifying glass of no more than 10 times, and the direction and morphology of the cracks on the first and second sections after acid immersion in the above-mentioned microscopic observation are observed using a microscope; the above-mentioned microscopic observations on the first and second sections are used to observe whether there is segregation of metal and non-metallic impurities at the cracks on the first and second sections, and whether there are abnormal precipitates at the crack edges of the first and second sections using an electron microscope. Thus, with different observation accuracies and different observation methods, observations are made from the external morphology of the cracks to the internal organizational morphology, and the observation methods and means from shallow to deep make the observation results more accurate, thereby making the final judgment result more accurate, avoiding waste and scrapping of the ingot.

[0052] The method of judging whether there is no crack in the ingot based on the crack characteristics of the ingot end face is applicable to the ingot prepared by the process of "electric furnace smelting → LF+VD refining → continuous casting of Φ390mm round ingot → slow cooling → finishing (continuous casting ingot low magnification detection) → forging and rolling finished product", and is particularly applicable to the manufacture of railway wheel steel continuous casting large round ingots and rolled wheel products thereof. The quality of railway wheel steel produced by the continuous casting round ingot process is significantly better than that of wheel steel produced by the die casting process. The continuous casting round ingot has high cleanliness, small segregation, dense lateral low magnification structure, good surface quality, and good product consistency. The defects of the ingot are mainly internal cracks.

[0053] In this embodiment, the diameter of the continuous casting large round billet applicable to the present invention includes but is not limited to products of any size specifications ranging from Φ300mm to Φ1000mm, and is particularly suitable for products of specifications such as Φ300mm, Φ390mm, Φ550mm, Φ690mm and Φ800mm.

[0054] Exemplarily, in order to test whether the above method of the present invention can accurately judge the cracks inside the ingot based on the cracks at the end of the ingot, the method of the present invention is used to detect the railway wheel steel ingot manufactured by the process of "electric furnace smelting → LF+VD refining → continuous casting Φ390mm round ingot → slow cooling → finishing (low-power detection of continuous casting ingot) → forging and rolling finished product". The steel is ER7 high-speed train wheel steel, which contains at least [C] = 0.50% ~ 0.52%, [Si] = 0.30% ~ 0.38%, [Mn] = 0.80% ~ 1.00%, [P] ≤ 0.015%, [S] = 0.004-0.013%. The defect requirements for cracks of the product are: subcutaneous cracks 0 level, intermediate cracks 0 level, and center cracks 0 level. The following is a detection of cracks on the end surface of a continuously cast round ingot with a diameter of Φ390mm and a rolled wheel product with a diameter of Φ918mm, including the following specific steps:

[0055] (1) Macrostructure analysis of round billet: Take the transverse macroscopic specimen of the end face of the above-mentioned ingot and conduct acid immersion macroscopic test. The specific gravity of hydrochloric acid used for sample corrosion is 1.19g / ml (concentration 39%), the sample corrosion time is 5-30min, the corrosion liquid composition is: hydrochloric acid water solution 1:1 (volume ratio), the temperature is 70-80℃. The test results of crack defects are: subcutaneous crack 0 level, middle crack 0 level, center crack 1.0 level, such as Figures 2 to 3 As shown, Figure 2 Schematic diagram of low-magnification observation of the center crack of a wheel steel round billet by acid immersion in order to judge that there is no crack in the billet based on the crack characteristics of the billet end surface. Figure 3 for Figure 2 A local enlarged schematic diagram of the crack is shown in the figure, and the length of the crack is measured with a ruler.

[0056] From the macroscopic morphology of the crack, it can be seen that the defect is a crack near the center of the ingot acid-etched sample. According to the characteristics of the steel grade, the C content of this steel grade is 0.50% to 0.52%, which is close to the end point of the peritectic reaction. The peritectic reaction of the molten steel during solidification is negligible, the heat flow during solidification is the largest, the directional heat transfer effect is significant, the columnar crystal is abnormally developed, the central equiaxed crystal area is the smallest, and the crack sensitivity is strong, so it is easy to produce central cracks and middle crack defects.

[0057] Metallographic analysis: Observe the transverse cross-sectional morphology of the low-magnification crack, cut the low-magnification crack from 1 / 2 of its length (vertical cutting), and observe the cross-sectional characteristics of the crack. Figures 4 to 7 ,in, Figure 4 For along Figure 2 Schematic diagram of the crack after vertical sectioning at the crack center shown in; Figure 5 for Figure 2 Schematic diagram of the metallographic structure of the cross section of the middle crack (second section), where Figure 5The position indicated by the middle circle is the crack and its location; Figure 6 for Figure 5 The schematic diagram of the partial enlargement of the metallographic structure of the crack cross section shown in Figure 6 The middle arrow shows the pickling surface of the continuous casting billet after pickling with corrosive liquid; Figure 7 To include Figure 5 Schematic diagram of the local enlarged structure of the end of the crack, where Figure 7 The arrow in the middle shows the morphology of the crack end.

[0058] (3) Scanning electron microscope analysis: observe the transverse cross-sectional morphology of low-magnification cracks, such as Figure 8 As shown, it includes Figure 5 The SEM local magnified structure diagram of the end of the crack, showing that the crack is extending along the crystal. Scanning electron microscopy showed that there was no large amount of Mn, S, P and other non-metallic inclusions segregated at the crack, and there was no abnormal precipitation phase at the edge of the crack, and the organization on both sides of the crack could be "completely spliced".

[0059] (4) Comprehensive analysis:

[0060] Combined with the above Figure 2-Figure 8 As shown in the figure, the low-magnification pickling surface of the crack on the low-magnification observation surface is a "straight-line" linear stress crack. A metallographic specimen is prepared from the observed crack on the low-magnification observation surface, which is used as the first section for microscopic observation. The crack is cut from 1 / 2 of the length (vertical cutting), and the cross-section of the crack is observed. It is found that the crack on the second section extends along the grain boundary of the cast structure in a "zigzag" shape. At the same time, metallographic and electron microscopic observations of the first and second sections show that the tissues on both sides of the crack can be "completely spliced" and meet the judgment conditions.

[0061] Combined with the knowledge of materials science, the above phenomenon can show that the crack starts from the surface of the low-magnification sample of the ingot, that is, the sawing surface of the ingot presents a "straight-line" shape, which is mainly transgranular, and then the crack extends to the inside of the ingot. At the same time, due to the gradual release and attenuation of stress, it extends along the grain boundary of the as-cast structure and presents a "zigzag" distribution, so it is mainly along the grain with a small amount of transgranular. It can be seen that the low-magnification cracks of the ER7 ingot are related to the residual stress of the ingot and form local surface cracks when the ingot is sawed and sampled. However, when the ingot is not sawed and sampled, there is no "central crack" inside the ingot.

[0062] In view of the situation that "the pickling surface of the round billet is a straight line transgranular stress crack with a zigzag cross-sectional shape" caused by high residual stress of the billet, the following method can be used to eliminate the existing cracks to improve or solve the problem of economic losses caused by internal defects of the billet.

[0063] Specifically, firstly, the continuous casting billet complete annealing process is used to eliminate the "center / middle crack" problem of ER7 round billets, which are characterized by "straight transgranular stress cracks on the pickling surface and zigzag cross-sectional shape (mainly along the crystal, with a small amount of transgranular)". Secondly, when the billet is not annealed, selecting an appropriate round billet heating process can eliminate the influence of residual stress in the billet, and at the same time can fully guarantee the physical quality of the product after rolling into a wheel.

[0064] In order to ensure that the above method is used to eliminate the crack defects inside the ingot, the ingot after the above heat treatment is verified, including:

[0065] First, a furnace of ER7 test steel with a total of Φ390mm×12 continuous casting billets (slowly cooled, weighing 75 tons) was selected, and low-power inspection was performed on each billet. The "center crack" defect rate was 50%, and the crack defect rating was 0.5-2.0; secondly, the furnace steel was subjected to a complete annealing process, such as Fig. 9 As shown, when annealing the continuous casting billet, first heat the continuous casting billet, and control the heating rate to be less than 50℃ / h during the heating process. When heated to 550-650℃, keep it warm for 3 hours, then heat the continuous casting billet again, and when heated to 720±10℃, keep it warm for at least 8 hours, then cool it down at a rate of less than or equal to 30℃ / h until the temperature drops to less than or equal to 250℃, then the continuous casting billet is taken out of the furnace, completing the complete annealing of the continuous casting billet. In the above-mentioned complete annealing process, the material will be heated to above its critical temperature, then kept warm for a period of time, and finally slowly cooled to room temperature; this process can solve the internal stress and defects of the material, restore the plasticity and toughness of the material, and improve the strength and hardness of the material. Adopting Fig. 9 After the annealing process shown, each piece was inspected at low magnification and the "center crack" defect rate was 0, and the crack defect rating was 0.

[0066] According to experimental results and practical applications, continuous casting round billets with low-magnification cracks not exceeding level 1.0 after acid immersion can be circulated normally, and there is no problem of economic losses caused by scrapping. In recent years, more than 100,000 tons of continuous casting round billets for ER7 high-speed train wheels have been stably produced and sold in accordance with the regulations that "continuous casting round billets with low-magnification cracks not exceeding level 1.0 after acid immersion can be circulated normally", which solves the problem of return / scrap in the next process based on "when continuous casting low-magnification cracks appear, it is impossible to judge whether the billet has no internal cracks". The quality of the finished wheels rolled in the next process is stable, and no quality problems of the finished wheels caused by the low-magnification "center crack / middle crack" defects of the billet have been found. No fatigue rim crack problems have been found in the service of the exported wheels, which can ensure the product safety of end users.

[0067] Therefore, the method of judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end face of the present invention comprehensively identifies and judges whether there are no internal cracks in the ingot based on the process characteristics such as "low-magnification organization + metallography + scanning electron microscope" analysis, crack anatomical morphology characteristics, segregation of Mn, S, P and other non-metallic inclusions at the crack, abnormal precipitation phase at the crack edge, and whether the organization on both sides of the crack can be "completely spliced". It solves the problem that it is difficult to determine "when low-magnification cracks of continuous casting ingots appear, whether such cracks already exist inside the ingot" by using ultrasonic flaw detection methods in the prior art, and the problem of returning / scrapping the ingot based on "when low-magnification cracks of continuous casting appear, it is impossible to determine whether the ingot has no internal cracks". At the same time, the method of judging whether there are no cracks in the ingot based on the crack characteristics of the ingot end face of the present invention also avoids huge economic losses by determining with the next process that "the low-magnification cracks of continuous casting round ingots acid leaching are not greater than 1.0 level and can be circulated normally". This method is highly operational and reproducible, and can eliminate human differences, truly and accurately reflect the crack conditions, and reflect the internal quality level of the material. It is of great significance for guiding the production process, optimizing the process, and formulating and revising industry standards.

[0068] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In addition, "front", "back", "left", "right", "upper" and "lower" in this article are all referenced to the placement state shown in the accompanying drawings.

[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for judging whether there are no cracks in a billet based on the characteristics of cracks on the end surface of the billet, characterized in that: include: The end face of the ingot sample is acid-diluted, the acid-diluted time is controlled to be 5-30min, the temperature of the solution during the acid-diluted process is controlled to be 70-80℃, and the end face of the ingot after acid-diluted is used as a low-magnification observation surface for macroscopic observation of cracks; A metallographic specimen is prepared for the observed crack on the low-magnification observation surface and used as a first section surface for microscopic observation, and the observed crack is sectioned along a preset position on the low-magnification observation surface in a direction perpendicular to the crack to obtain a second section surface, and the direction and morphology of the crack on the first section surface and the second section surface are microscopically observed; Microscopically observing whether there is segregation of metal and non-metal impurities at the cracks on the first section surface and the second section surface, and whether there is abnormal precipitation phase at the edge of the cracks on the first section surface and the second section surface; Whether cracks already exist inside the ingot can be determined based on the direction and shape of cracks on the low-magnification observation surface, the first section surface, and the second section surface of the ingot sample.

2. The method for judging whether there are no cracks in a cast billet according to the crack characteristics of the end surface of the cast billet according to claim 1, characterized in that: The cracks include any one or more of central cracks, middle cracks and subcutaneous cracks on the end surface of the ingot.

3. The method for judging whether there is no crack in the ingot according to the crack characteristics of the ingot end surface according to claim 1, characterized in that: Acid immersion of the end surface of the ingot sample includes acid immersion using a corrosive liquid.

4. The method for judging whether there is no crack in the ingot according to the crack characteristics of the ingot end surface according to claim 3, characterized in that: The etching solution includes a hydrochloric acid aqueous solution with a volume ratio of 1:

1.

5. The method for judging whether there is no crack in the ingot according to the crack characteristics of the ingot end surface according to claim 4, characterized in that: The hydrochloric acid selected in the hydrochloric acid aqueous solution includes a hydrochloric acid solution with a specific gravity of 1.19 g / ml or a concentration of 39%.

6. The method for judging whether there is no crack in the ingot according to the crack characteristics of the ingot end surface according to claim 1, characterized in that: The preset position includes a position at half the crack length.

7. The method for judging whether there is no crack in the ingot according to the crack characteristics of the ingot end surface according to claim 1, characterized in that: Judging whether cracks already exist inside the ingot based on the direction and shape of cracks on the low-magnification observation surface, the first section surface and the second section surface of the ingot sample, including: Determine whether the crack shape on the low-magnification observation surface and the first section surface after acid immersion is a straight line or a linear type; Determine whether the crack on the second section surface extends in a zigzag shape along the grain boundary of the as-cast structure, and whether the structures on both sides of the crack on the first section surface and the second section surface can be completely spliced; Determine whether there is segregation of metal and non-metal impurities at the cracks on the first section surface and the second section surface, and whether there is abnormal precipitation phase at the edge of the cracks on the first section surface and the second section surface; If the morphology of the cracks observed on the low-magnification observation surface and the first section surface is a straight line or a linear shape, the cracks observed on the second section surface crack and expand in a zigzag shape along the grain boundary of the as-cast structure, the structures on both sides of the crack on the first section surface and the second section surface can be completely spliced ​​together, there is no segregation of metal and non-metallic impurities at the cracks on the first section surface and the second section surface, and there are no abnormal precipitated phases at the crack edge positions on the first section surface and the second section surface, then there are no cracks inside the ingot, otherwise there are cracks inside the ingot.

8. The method for judging whether there is no crack in the ingot according to the crack characteristics of the ingot end surface according to claim 1, characterized in that: The macroscopic observation includes observation with the naked eye or observation with a magnifying glass of no greater than 10 times.

9. The method for judging whether there is no crack in the ingot according to the crack characteristics of the ingot end surface according to claim 1, characterized in that: The microscopic observation includes observation using a metallographic microscope or a scanning electron microscope.